2007
DOI: 10.1016/j.expneurol.2006.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and toxicity induced by the nucleoside reverse transcriptase inhibitor (NRTI)—2′,3′-dideoxycytidine (ddC): Relevance to HIV-dementia

Abstract: Human immunodeficiency virus dementia (HIVD) is the most common form of dementia occurring among young adults. In HIVD, neuronal cell loss occurs in the absence of neuronal infection. With the advent of highly active anti-retroviral therapy (HAART), the incidence of HIVD has drastically reduced, though prevalence of milder forms of HIVD continues to rise. Though these agents have been used successfully in suppressing viral production, they have also been associated with a number of side effects. Here we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 76 publications
2
38
0
Order By: Relevance
“…However, other 1 H-MRS studies found either no change or even improvement in NAA or NAA/creatine in patients treated with ARVs (Chang et al 1999Tarasow et al 2004;Vion-Dury et al 1995), although most studies did not distinguish those treated with NRTIs from those on non-NRTIs. A preclinical study also found that ddC, but not 3TC, at CSF-achievable concentrations, induced oxidative stress and increased proteins associated with induction of apoptosis (Opii et al 2006). Therefore, whether NRTIs may contribute to brain injury that could exacerbate HIV dementia or cognitive impairment remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, other 1 H-MRS studies found either no change or even improvement in NAA or NAA/creatine in patients treated with ARVs (Chang et al 1999Tarasow et al 2004;Vion-Dury et al 1995), although most studies did not distinguish those treated with NRTIs from those on non-NRTIs. A preclinical study also found that ddC, but not 3TC, at CSF-achievable concentrations, induced oxidative stress and increased proteins associated with induction of apoptosis (Opii et al 2006). Therefore, whether NRTIs may contribute to brain injury that could exacerbate HIV dementia or cognitive impairment remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…D609 mimics glutathione (GSH) and has a free thiol group, which upon oxidation forms a disulfide. The resulting dixanthate is a substrate for glutathione reductase, regenerating D609 (Joshi et al 2005;Opii et al 2007).…”
Section: Oxidative Stress Apoptosis and Abmentioning
confidence: 99%
“…Evidentially, the levels of HepG2 cell proliferation and viability, and their mitochondrial DNA contents in the compound-treated cells were similar to that of untreated controls. Long-term treatments with antiviral nucleotide analogs are associated with severe mitochondrial toxicity due to the incorporation of nucleotide analogs or the termination of DNA replication (Dusheiko and Antonakopoulos, 2008;Gordon, 1996;Opii et al, 2007;Prince, 1996). The very low cytotoxicity of those novel derivatives of adefovir, together with their high anti-HBV activities, suggests that they may be relatively safe for long-term treatments of HBV infection.…”
Section: Discussionmentioning
confidence: 99%